K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

23 tháng 11 2021

x3-2x2-25xy2+x

=x(x2-2x+1-25y2)

=x[(x-1)2-25y2]

=x(x-1-5y)(x-1+5y)

15 tháng 1 2019

a.

\(125xy-25xy^4=25xy\left(5-y^3\right)\)

b.

\(x^3-2x^2-x+2=x^2\left(x-2\right)-\left(x-2\right)=\left(x-2\right)\left(x^2-1\right)=\left(x-2\right)\left(x-1\right)\left(x+1\right)\)

25 tháng 11 2017

2/

\(x^3-2x+1=0\)

\(\Rightarrow x^3-x-x+1=0\)

\(\Rightarrow x\left(x^2-1\right)-\left(x-1\right)=0\)

\(\Rightarrow x\left(x-1\right)\left(x+1\right)-\left(x-1\right)=0\)

\(\Rightarrow\left(x-1\right)\left(x^2+x-1\right)\)

\(\Rightarrow x=1\)

Vậy S = {1}

2 tháng 8 2018

\(\left(x+y\right)^3-x^3-y^3\)

\(=x^3+3x^2y+3xy^2+y^3-x^3-y^3\)

\(=3x^2y+3xy^2\)

\(=3xy\left(x+y\right)\)

2 tháng 8 2018

\(a,\left(2x+3y\right)^2-4\left(2x+3y\right)\)

\(=\left(2x+3y\right)\left(2x+3y-4\right)\)

\(b,\left(x+y\right)^3-x^3-y^3\)

\(=\left(x+y\right)^3-\left(x^3+y^3\right)\)

\(=\left(x+y\right)\left[\left(x+y\right)^2-\left(x^2-xy+y^2\right)\right]\)

\(=\left(x+y\right).3x\)

\(c,\left(x-y+4\right)^2-\left(2x+3y-1\right)^2\)

\(=\left(x-y+4+2x+3y-1\right)\left(x-y+4-2x-3y+1\right)\)

\(=\left(3x+2y+3\right)\left(-x-4y+5\right)\)

19 tháng 6 2019

b, \(2x+4x^2=5-5+4-2^2\)

\(\Leftrightarrow2x\left(1+2x\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}2x=0\\1+2x=0\end{cases}}\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=-\frac{1}{2}\end{cases}}\)

Vậy...

19 tháng 6 2019

\(2x+4x^2=5-5+4-2^2\)

\(\Leftrightarrow2x+4x^2=0\)

\(\Leftrightarrow4x^2+2=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=-\frac{1}{2}\end{cases}}\)

Vậy:...

21 tháng 7 2016

1) (x-2)3

2) (x-1+5x)(x-1-5x)=(6x-1)(-4x-1)

3) (6x-2x-1)(6x+2x+1)=(4x-1)(8x+1)

4) (x+3-2x+1)(x+3+2x-1) = (4-x)(3x+2)ok

21 tháng 7 2016

1. \(x^3-6x^2+12x-8=\left(x-2\right)^3\)

2. \(\left(x-1\right)^2-25x^2=\left(x-1-5x\right)\left(x-1+5x\right)\)

\(\left(-4x-1\right)\left(6x-1\right)\)

3. \(36x^2-\left(2x+1\right)^2=\left(6x-2x-1\right)\left(6x+2x+1\right)\)

\(\left(4x-1\right)\left(8x+1\right)\)

4. \(\left(x+3\right)^2-\left(2x-1\right)^2=\left(x+3-2x+1\right)\left(x+3+2x-1\right)\)

\(\left(4-x\right)\left(3x+2\right)\)

Chúc bạn làm bài tốt